Renaissance of vancomycin: approaches for breaking antibiotic resistance in multidrug-resistant bacteria - Mühlberg, Eric; Umstätter, Florian; Kleist, Christian; Domhan, Cornelius; Mier, Walter; Uhl, Philipp (Canadian journal of microbiology, 2020)
The emergence of multidrug-resistant bacteria demands innovations in the development of new antibiotics. For decades, the glycopeptide antibiotic vancomycin has been considered as the “last resort” treatment of severe infections caused by Gram-positive bacteria. Since the discovery of the first vancomycin-resistant enterococci strains in the late 1980s, the number of resistances has been steadily rising, with often life-threatening consequences. As an alternative to the generation of completely new substances, novel approaches focus on structural modifications of established antibiotics such as vancomycin to overcome these resistances. Here, we provide an overview of several promising modifications of vancomycin to restore its efficacy against vancomycin-resistant enterococci.